Klassifikacija slavjanskih jazykov na materiale Obščeslavjanskogo lingvističeskogo atlasa - Kuz'mina, Anastasija Sergeevna (Slovenski jezik, 2025)
This article proposes an innovative classification methodology for Slavic languages based on data from the The Slavic Linguistic Atlas (OLA). The approach employs pairwise comparison of Proto-Slavic vowel reflexes across 780 settlements. Applying hierarchical clustering algorithms to a matrix of dialect proximity measures, we have identified 15 distinct linguistic areas within the Slavic continuum. For each delineated area, we provide both formal linguistic descriptions and theoretical interpretations.
Keywords: classification; dialectometry; dialektometrija; klasifikacija; Slavic languages; Slavic linguistic atlas; slovanski jeziki; Slovanski lingvistični atlas